TSX-Data for Studies of Snow on Ice Sheets and Sea Ice - Preliminary Results - Dierking, W.; Linow, S.; Wesche, C.; Rack, W.; Hoppmann, M.; Willmes, S. (University of Canterbury. Gateway Antarctica, 2013)
The balances between mass gain and loss of the ice sheets and of the polar sea ice have received increased attention because of their influence on changes of Earth’s environment. In this context, investigations of snow accumulation on ice sheets and snow load on sea ice are important topics of recent research. This short note motivates the need for such investigations. First results addressing snow accumulation rates over Dronning Maud Land (Antarctica) and snow deposition on sea ice in Atka Bay (Dronning Maud Land) obtained from TSX images are presented.